m-Health application, a mobile/web-based application making real-time information on service delivery and beneficiary nutrition status available to community-based health workers - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
A consortium of research partners conducted the process evaluation of this m-Health innovation, and some findings informed improvements. The endline survey for the study (Evaluation of the Integrated Child Development Services - Common Application Software (ICDS-CAS) in Madhya Pradesh and Bihar) is ongoing.